Representations of the concept of independence at the beginnings of the Paraguayan press (1845-1852) (2021)
The present work proposes to analyze the political concepts and representations deployed around the search for recognition of the Independence of Paraguay by the Argentinian Confederation. The chosen source is the press, a privileged environment of the political debate. The focus was put on the study of El Paraguayo Independiente, the first newspaper of Paraguay which was created during the government of Carlos Antonio López in 1845. Its principal writer was the Paraguayan president himself. The initial difficulty of defining the concept of Independence in Paraguay was a relevant part of the diplomatic conflicts with its neighbors and of the antecedents to the great war.